Cardiovascular Simulation Cases for Dental Students - Kenneth Roos; Sebastian Uijtdehaage; Courtney Gordon; Shadi Kamyab (Association of American Medical Colleges, 2009)
Abstract Introduction Human patient simulation (HPS) exercises are now routinely used in medical school for teaching physiologic principles in a clinical context without patient risks. The use of HPS in dental education, however, is still exceedingly rare. As part of a basic physiology course, we developed two HPS-based cases to expose first-year dental students to the physiological processes related to the most common acute cardiovascular emergencies that occur during daily dental practice. Methods The students were first introduced to a high-fidelity HPS during a lecture and reviewed the objective for the subsequent laboratory. The two laboratory simulation cases focused on diagnosis and management of neurogenic shock and the angina pectoris that may occur during dental treatment. During the scenarios, the basic physiological events were tied to real clinical situations. This innovative model of dental education was designed to provide hands-on experience for managing a cardiovascular emergency in dental practice and for improving conceptual knowledge in critical clinical decision making. Results To date, HPS is rarely used in dental education. Our case scenarios demonstrate an effective use of HPS for exposing dental students to two of the most common acute cardiovascular medical emergencies that can occur in dental practice. They provided the first-year students with skills early in their training, prior to their first encounter with a live patient in a clinical setting. Compared to historic controls, students did not show significant differences in their overall exam scores. However, there was one question on the electrocardiogram arrhythmias which asked about atrial fibrillation which was shown with the simulator exercise in 2008 and not in 2007. Students did significantly better on that question. Discussion The simulation is useful to illustrate the pathophysiological events underlying cardiovascular emergencies that may occur in dental practice. In future years, each scenario will be evaluated separately. The 50-minute introductory lecture and short active simulation based-discussion worked very well at introducing students to the simulation as part of their new curriculum and saved more time for their first lab session.